SITEM INFORMASI GEOGRAFIS SEBARAN PELANGGAN PERUSAHAAN DAERAH AIR MINUM (PDAM) DI KABUPATEN JEPARA TAHUN 2020 & 2021 - Muhammad Vendi Nur Rohim; Bambang Agus Herlambang, Ahmad Khoirul Anam (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
Water is one of the building blocks of the human body. With a percentage of around 70% in the human body, water is important for survival. Humans use water in everyday life for various purposes such as washing, cooking, drinking water, bathing and others. The water usually used is ground water. However, not all groundwater houses have good quality for drinking or cooking water. Knowing this problem, the central government, through regional governments, established regional drinking water companies (PDAM) in each region to provide drinking water that is clean, healthy and meets health requirements for the community, which is also a form of service provided by the government to the community. This PDAM is considered not to have reached all regions so a system is needed that is able to provide data quickly. The rapid development of information technology in the current era of globalization provides many benefits in progress, one of which is geographic information. The Quantum GIS application can be used to create, edit, visualize, analyze, and process geospatial information. Quantum GIS can visualize spatial data and non-spatial data involved in this research. The aims and objectives of this research are to design and build a program that makes it easier for various parties such as the community and government to facilitate data management by utilizing geographic information systems in mapping regional drinking water company (PDAM) customers.